Synthesis and characterization of β-TCP/CNT nanocomposite: Morphology, microstructure and in vitro bioactivity. Issue 10 (July 2017) - Mirjalili, Fatemeh; Mohammadi, Hossein; Azimi, Mohammad; Hafezi, Masoud; Abu Osman, Noor Azuan
Abstract: In this study, β-TCP/CNT nanocomposite has been synthesized by solution precipitation method. Then, the effects of the different percentage of CNT (CNT1β-TCP, CNT3β-TCP, CNT5β-TCP) and surfactant (CNT1β-TCP1SDBS, CNT1β-TCP2SDBS, CNT1β-TCP3SDBS) on β-TCP/CNT nanocomposite powder were studied. The X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and Transmission electron microscopy (TEM) analyses were used to characterize the samples. The observations revealed that the microstructure of 1 wt% CNT could provide dispersion without agglomeration in nanocomposite powder; however, a higher concentration of CNT powder in the nanocomposite resulted in the formation of Ca2 PO7 phase. Implementing 2 wt% of SDBS as a surfactant modified the shape, size, and distribution of CNT particles on nanocomposites. Finally, the nanocomposite sample was immersed in simulated body fluid (SBF) to evaluate the in vitro bioactivity. It obviously showed an apatite layer on the surface after 7 days of immersion in SBF. Taken together, this nanocomposite might be potentially to be used as bone repair biomaterial.